Gene Expression of Subtilisin Genes of UV-irradiated Trichophyton indotineae Isolated from Iraqi Patients - Hendi, Aseel H.; Al-Araji, Alaa M. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Virulence genes in dermatophytes have been a major focus of research in recent years. These fungi have a unique ability to degrade keratin, an essential structural protein in human skin, using protease enzymes. These enzymes play a crucial role in the development and spread of infections. Objectives: To assess the impact of UV radiation on the expression of subtilisin virulence genes in Trichophyton indotineae isolates obtained from patients in Baghdad, Iraq. Materials: Seven T. indotineae isolates were analyzed in this study, and their proteolytic activity was qualitatively assessed using skim milk agar. The isolate displaying the largest clearance zone in response to UV radiation (254–365 nm) was selected for further experiments with varying exposure durations. The expression of Subtilisin (SUB) genes was measured using the one-step RT-qPCR technique. These specimens were obtained from patients diagnosed with Tinea at Al-Yarmouk Teaching Hospital and Al-Zahra Consultative Center for Allergy and Asthma in Baghdad, and the laboratory procedures were conducted in the Department of Biology, College of Science, University of Baghdad, between October 2022 and February 2023. Results: Distinct trends in SUB7 gene expression were observed following UV exposure. A significant increase was noted after 6 minutes of exposure to 365 nm UV, while a rapid rise was seen after 3 minutes of exposure to 254 nm UV. All the studied genes (SUB1, SUB3, SUB4, SUB6, and SUB7) exhibited higher expression levels following UV exposure for 3 or 6 minutes. Most genes were upregulated, except SUB3, which was repressed after 12 minutes of exposure to 254 nm UV. Conclusion: The findings suggest that increased virulence gene expression may be a stress response to UV radiation, potentially influenced by rising global temperatures and increased solar irradiance during Iraqi summers.